Coaches` perceptions of innovation programs of the Royal Spanish Tennis Federation - Crespo, M.; Botella-Carrubi, D.; Jabaloyes, J. (International Journal of Sports Science & Coaching, 2021)
This research studied the coaches` perceptions of the innovation programs of the Royal Spanish Tennis Federation (RFET) during 2016-2020. The RFET is one of the most relevant national federations in Spain both in terms of results at the highest levels of the game as well as in terms of participation and grassroots tennis. Coaches are considered relevant stakeholders of any sport federation due to their role in delivering the sport. A 29-item questionnaire adapted to tennis was completed by 132 certified coaches RFET members which had different years of experience and coached players of various skill levels. Results showed significant differences between the coaches with more than 20 years of experience as they perceived more rivalry between regional federations in the access to grants and more international competitiveness at high-level tennis as compared to their less experienced colleagues. Coaches also considered that the COVID-19 pandemic had negatively affected the innovation strategy and capability of the organization. They identified a grassroots initiative and a coach education project as the two most valued innovative programs implemented by the RFET in the period. These last findings coincide with those from previous research and highlight the relevance of providing coaches with clear player development guidelines and opportunities for continuous professional development through education. It can be concluded that federation leaders should consider the coaches` perceptions on their innovation programs. This will assist them to better provide initiatives that will satisfy their needs and improve the effectiveness of their federations.